Diskriminasi dan Peminggiran Jurnalis Perempuan dalam Industri Media di Indonesia - Famega Syavira Putri (Ikatan Sarjana Komunikasi Indonesia, 2025)
Abstract - Female journalists in Indonesia continue to experience various forms of discrimination and marginalization, even within the media institutions where they work. This inequality is evident not only in daily professional practices but also in access to strategic positions in newsrooms. This paper aims to examine the condition of women’s leadership in Indonesian media organizations as well as the realities faced by female journalists in carrying out their profession. Findings that indicate the persistence of gender-based discrimination and inequality in leadership positions within newsrooms can be more deeply understood through the framework of muted group theory, which emphasizes how subordinate groups are structurally constrained in expressing their experiences and interests within communication systems dominated by those in power. This study employs a literature review method using secondary data sources. A review of 16 scholarly works shows that female journalists continue to face discrimination based on gender, including role stereotyping, gender-biased assignment of news coverage, and the double burden of balancing professional work with domestic responsibilities. Moreover, women’s representation in top leadership positions within the media remains very limited. Of the 1,861 media organizations registered with the Press Council, only 65 are led by women. These findings indicate that the structure of the media industry in Indonesia has not yet become fully inclusive of women, both as media workers and as decision-makers.Keywords: Journalism, Women, Leadership, Gender Equality, Muted Group TheoryAbstrak - Jurnalis perempuan di Indonesia hingga kini masih menghadapi berbagai bentuk diskriminasi dan peminggiran, bahkan di dalam institusi media tempat mereka bekerja. Ketimpangan ini tidak hanya terlihat dalam praktik kerja sehari-hari, tetapi juga dalam akses terhadap posisi strategis di ruang redaksi. Tulisan ini bertujuan untuk memformulasikan bagaimana kondisi kepemimpinan perempuan di perusahaan media di Indonesia serta bagaimana realitas yang dihadapi jurnalis perempuan dalam menjalankan profesinya. Temuan-temuan yang menunjukkan masih kuatnya diskriminasi berbasis gender serta ketimpangan dalam posisi kepemimpinan di ruang redaksi dapat dipahami secara lebih mendalam melalui kerangka muted group theory, yang menekankan bagaimana kelompok subordinat dibatasi dalam menyuarakan pengalaman dan kepentingannya dalam struktur komunikasi yang didominasi kelompok berkuasa. Penelitian ini menggunakan metode ulasan literatur dengan pengambilan data sekunder. Ulasan terhadap 16 literatur menunjukkan bahwa jurnalis perempuan masih mengalami diskriminasi berdasarkan gender, termasuk stereotip peran, pembagian liputan yang bias, serta beban ganda antara pekerjaan profesional dan tanggung jawab domestik. Selain itu, representasi perempuan dalam posisi puncak kepemimpinan media juga masih sangat rendah. Dari 1.861 perusahaan media yang tercatat di Dewan Pers, hanya 65 media yang dipimpin oleh perempuan. Temuan ini menegaskan bahwa struktur industri media di Indonesia masih belum sepenuhnya inklusif terhadap perempuan, baik sebagai pekerja maupun sebagai pengambil keputusan.Kata kunci: Jurnalisme, Perempuan, Kepemimpinan, Kesetaraan Gender, Muted Group Theory